Sustainable growth and resource productivity : economic and global policy issues. - Bleischwitz, Raimund, ....-; Welfens, Paul J. J., 1957-; Zhang, Zhongxiang, 1963- (Sheffield : Greenleaf, 2009)
Written by international experts in their respective field, "Sustainable Growth and Resource Productivity" provides a comprehensive overview of global issues of raw materials supply and resource use. It also introduces new views and perspectives on the sustainable growth of emerging economies and develops a rationale for a new resource economics. This book emphasises why resources are back on the agenda: firstly, because of their fundamental economic role in technological progress and long-term prosperity; secondly, because deficits in raw material markets are now intertwined with deficits in the financial markets; and, thirdly, because the sustainable management of natural resources is a crucial element in responses to new global challenges such as climate change. "Sustainable Growth and Resource Productivity" analyses raw materials supply and resource use in a global context. The contributions present state-of-the-art results and perspectives on the availability of resources and discuss
Factors such as limited supply, demand from emerging and other economies and the critical shortage of some materials - particularly some metals - that are essential inputs in many high-tech processes and may put certain industries at risk. "Sustainable Growth and Resource Productivity" sheds new light on the economics of sustainable growth. Linking the current financial crisis with stock market pricing and innovation dynamics, it argues for reforms in international macro-economic policies. It also critically discusses the implications of valuing labour productivity over capital and resource productivity and argues that policies favouring capital productivity will increase both social and economic sustainability. Further contributions are made on the business dimensions of material efficiency as well as on policy recommendations. The book examines the overall empirical trend towards decoupling resource use from economic growth. It undertakes a rigorous cross-country comparison and looks in
More detail at the cases of Finland and Greece, as well as at emerging economies and their role in the global governance of natural resources. A key focus is placed on China, with discussion of recent findings regarding Chinese domestic policy on energy, climate and resources as well as on developing Chinese foreign policy in Africa. The book concludes with the positing of a new theory of resource economics: an emerging sub-discipline that puts resources at its heart but clearly aligns with other fields of economics, and transcends the borderlines of geology, geography, material science, recycling and waste, as well as elements of other social sciences. This important new book will be essential reading for economic researchers, governmental officials, businesses and NGOs with an interest in understanding the policy links to sustainable growth and in learning more about the emerging field of resource productivity.
Keywords: Duurzame economie